PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE BERKIRIM SALAM DAN SOAL UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 003 KAMPAR UTARA - Harmilas '; Syahrilfuddin '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes IPS Grade IV SDN 003 Kampar Utara. This research was conducted in the fourth grade SDN 003 Kampar Timur, while the time the study was conducted in the academic year 2015/2016. Design of this research is the Classroom Action Research (PTK). As the subjects in this study were teachers and students of class IV SDN 003 Kampar Utara, with the number of 16 students, consisting of 10 men and 6 women. From the results, it can be concluded the implementation of cooperative learning model send greetings and questions can improve learning outcomes IPS grade IV SDN 003 Kampar Utara. The increase of the average score of the base to the first cycle at an average of 59.81 into 68.44 with an increase of 8.63. An increase from the first cycle to the second cycle, ie from an average of 68.44 into 78.13 with an increase of 9.69. Increased activity of teachers at the first meeting of all the components found to be the percentage of 63% with good criterion. While in the first meeting of the second cycle teachers get a percentage of 92% and increased in the second meeting to 96%. Likewise, the students' activity wherein the activity of students in the first cycle have gained 1 percentage meetings by 63% and 2 by 75%. In the first cycle obtained by students who pass by 75% and in the second cycle students obtained completeness of 100%. While the basic score obtained completeness 63%. Key Words: learning outcomes IPS, exchanging greetings and questions